Aspectos tradutórios em Ma vie ne sait pas nager de Élaine Turgeon - Donadio, Glenda Verônica [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The work Translational aspects in Ma vie ne sait pas nager by Élaine Turgeon approaches the entire translation process of this francophone children's work. The theme choice was due to the interest in deepening the translational knowledge, in addition to performing an analysis of the own translation work done. Thus, the theoretical aspects related to the translation are reported throughout the work, a succinct exhibition of the history of translation, a brief view of the children's editorial market (in the world and more specifically in Brazil), the book theme and author style, and finally, the drawbacks overcome during the realization of the work - based upon the theoretical body of work consulted - and the solution encountered for this. At the end of this same work, some considerations are drawn, as well as some reflections upon the translation realized (with the studied texts attached in the body of work); accompanied by some findings observed concerning the theory

O trabalho Aspectos tradutórios em Ma vie ne sait pas nager de Élaine Turgeon aborda todo o processo de tradução dessa obra infantojuvenil francófona. A escolha desse tema se deu pelo interesse no aprofundamento dos conhecimentos tradutórios além da realização de uma análise acerca da própria tradução realizada. Desse modo, são relatados ao longo desse trabalho os aspectos teóricos referentes à tradução, uma exposição sucinta sobre a história da tradução, um breve panorama acerca do mercado editorial das obras infantojuvenis (no mundo e, com mais especificidade, no Brasil), a temática do livro e estilo da autora e, por fim, os percalços enfrentados ao longo da realização dessa tradução - com base na teoria consultada - e as soluções encontradas para a resolução destes. Ao fim desse mesmo trabalho, são tecidas algumas considerações, como também, algumas reflexões em relação à tradução realizada (juntamente com os textos estudados inseridos no corpo do trabalho); aliadas à algumas constatações observadas referentes à teoria
Keywords: Turgeon, Élaine 1970- Ma vie ne sait pas nager; Literatura infantojuvenil - História e crítica; Traduções; Translations